Integration of Risk Thresholds into Enterprise Risk Management (ERM) Implementation in An Energy Company - Willy Januardi; Putu Dana Karningsih; Demi Ramadian (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
All state-owned enterprises are obligated to implement risk management effectively. Risk management implementation can be assessed using the Risk Maturity Index (RMI). The 2024 RMI assessment at one of the state-owned energy subsidiaries indicated that the Company is at the